Partisipasi Masyarakat Lokal Dalam Perusahaan BMW Rafting Di Desa Rendang, Kecamatan Rendang, Kabupaten Karangasem - I Nengah Sastrawan; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
Tourism is one of the industry sectors that contribute to the economy in the form offoreign exchange for many countries. With the presence of tourism will be the creation of new jobs. The participation of local communities in the company existing in its territory rafting will give rise to a sense of belonging to a destination. This research aims to know the participation of local communities in the BMW company rafting in the village of Rendang. Method of data collection is done by the way of observasi, in- depth interviews, and the study of librarianship. The technique of determination of the informant is done by means of purposive sampling, this research included in the qualitative research generates data deskriftif. With the presence of tourism opportunities, then revealing the many job opportunities that are owned by local people. Especially on a rafting company BMW employs local people as employees. With the involvement of local communities in the absorption of labor in the company of rafting can help boost the economy of local communities so that local communities can participate in the company as well as participate in maintaining the tourism destinations Keywords : Community Participation, Tourism Management, Bali Mitra Wahana Rafting